2006
DOI: 10.1111/j.1467-789x.2006.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Citrus aurantium and synephrine alkaloids in the treatment of overweight and obesity: an update

Abstract: Obesity is a major health problem facing the developed and developing world. Efforts by individuals, health professionals, educators, and policy makers to combat the escalating trend of growing obesity prevalence have been multifaceted and mixed in outcome. Various dietary supplements have been marketed to reduce obesity. These products have been suggested to accomplish this by decreasing energy intake and energy absorption, and/or increasing metabolic rate. Ephedra, one such supplement, was banned from sale i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
145
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 67 publications
4
145
0
3
Order By: Relevance
“…Synephrine has been reported to act on α-adrenoceptors (4) and to reduce portal pressure and elevate mean arterial pressure in sham-operated and portal hypertensive rats (5). Moreover, synephrine has been reported to have anti-obesity activity (6), exerted through its action on β 3 -adrenoceptors, which function to activate lipolysis. In addition, synephrine has been reported to have antidepressant-like effects (7).…”
Section: Introductionmentioning
confidence: 99%
“…Synephrine has been reported to act on α-adrenoceptors (4) and to reduce portal pressure and elevate mean arterial pressure in sham-operated and portal hypertensive rats (5). Moreover, synephrine has been reported to have anti-obesity activity (6), exerted through its action on β 3 -adrenoceptors, which function to activate lipolysis. In addition, synephrine has been reported to have antidepressant-like effects (7).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits of Citrus aurantium L. (Rutaceae family), commonly known as bitter orange, sour orange or Seville orange, are used as food, but this popular plant is more commonly used as a medicinal or dietary supplement (Fugh-Berman and Myers 2004). Similar to ephedra, it contains alkaloids that are adrenergic agonists and is often incorporated into supplements designed to aid in weight loss (Haaz et al 2006). It was confirmed that its essential oil has an antibiotic effect against Helicobacter pylori (Bergonzelli et al 2003).…”
Section: Introductionmentioning
confidence: 79%
“…The substances that reduce body weight are similar to ephedra, a component of the fruit, that contains alkaloids that are adrenergic agonists and is often incorporated to supplements designed to aid in weight loss (Preuss et al 2002). In some reports, Citrus aurantium products were combined with other agents, making it unclear which caused the benefit (Haaz et al 2006). …”
Section: Anomaly Frequencymentioning
confidence: 99%
“…1), which lower adipose tissue weight. 23,24 RK has also been reported to exert anti-obesity action and alter lipid metabolism. 25,26 We, therefore, analyzed whether RK has a positive effect on osteogenesis, because there has been no report on its effect on bone formation.…”
Section: Introduction Bmentioning
confidence: 99%